Tuberculous Pachymeningitis Presenting as a Diffused Dural Thickening in a Patient with Chronic Headache and Recurrent Neurological Abnormalities for More than a Decade: A Case Report and a Review of the Literature - C. L. Fonseka; T. E. Kanakkahewa; S. D. A. L. Singhapura; J. S. Hewavithana; L. P. Kolambage; H. M. M. Herath; K. D. Pathirana; Thilak Priyantha Weeraratna (Case Reports in Infectious Diseases)
Background. Tuberculous pachymeningitis is a rare form of extrapulmonary tuberculosis usually suspected from the detection of thickening of the dura in contrast-enhanced magnetic resonance imaging. Progressive nature of the disease can lead to chronic headache with focal neurological signs due to compression from the thickened dura. Case Report. We report a 40-year-old female who presented with chronic headache over a decade associated with recurrent neurological abnormalities including optic neuritis, hemisensory loss, migraine, facial nerve palsy, and recurrent vertigo. Although there was an initial perceived response to steroids, the patient had a subsequent progressive course. On investigations, she was found to have a diffused dural thickening on contrast MRI with a strongly positive Mantoux test with caseating necrotizing granulomatous inflammation on dural histology. With initiation of antituberculous medication with steroids, the patient markedly improved, and the medication for tuberculosis was continued for a year with good response. Conclusion. Primary tuberculous pachymeningitis should be suspected in a patient complaining of prolonged headache with focal neurological signs when MRI evidence of dural thickening is detected, and another focus of tuberculosis was not found. Prompt suspicion with image-guided dural biopsy for histology would help to confirm the diagnosis.